A BRIEF OPPORTUNITY TO RUN DOES NOT FUNCTION AS A REINFORCER FOR MICE SELECTED FOR HIGH DAILY WHEEL‐RUNNING RATES - Belke, Terry W.; Garland, Theodore (Journal of the experimental analysis of behavior, 2007)
Mice from replicate lines, selectively bred based on high daily wheel‐running rates, run more total revolutions and at higher average speeds than do mice from nonselected control lines. Based on this difference it was assumed that selected mice would find the opportunity to run in a wheel a more efficacious consequence. To assess this assumption within an operant paradigm, mice must be trained to make a response to produce the opportunity to run as a consequence. In the present study an autoshaping procedure was used to compare the acquisition of lever pressing reinforced by the opportunity to run for a brief opportunity (i.e., 90 s) between selected and control mice and then, using an operant procedure, the effect of the duration of the opportunity to run on lever pressing was assessed by varying reinforcer duration over values of 90 s, 30 min, and 90 s. The reinforcement schedule was a ratio schedule (FR 1 or VR 3). Results from the autoshaping phase showed that more control mice met a criterion of responses on 50% of trials. During the operant phase, when reinforcer duration was 90 s, almost all control, but few selected mice completed a session of 20 reinforcers; however, when reinforcer duration was increased to 30 min almost all selected and control mice completed a session of 20 reinforcers. Taken together, these results suggest that selective breeding based on wheel‐running rates over 24 hr may have altered the motivational system in a way that reduces the reinforcing value of shorter running durations. The implications of this finding for these mice as a model for attention deficit hyperactivity disorder(ADHD) are discussed. It also is proposed that there may be an inherent trade‐off in the motivational system for activities of short versus long duration.